The efficacy of neoadjuvant EGFR-TKI therapy combined with radical surgery for stage IIIB lung adenocarcinoma harboring EGFR mutations: A retrospective analysis based on single center - Xiong, Yicheng; Bian, Dongliang; Huang, Zhida; Yu, Huansha; Huang, Jie; Zhang, Peng; He, Wenxin; Liu, Hongcheng (Frontiers in Oncology, 2023)
Background Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) could provide survival benefits for locally advanced EGFR-mutant (EGFRm) non-small cell lung cancer (NSCLC). However, the role of radical surgery for EGFR-TKI treated stage IIIB EGFRm NSCLC remains controversial. This study attempted to assess the feasibility of neoadjuvant EGFR-TKI followed by radical surgery for stage IIIB EGFRm NSCLC. Patients and Methods Between 2013 and 2020, EGFRm lung adenocarcinoma (LUAD) patients in clinical stage IIIB undergoing neoadjuvant EGFR-TKI followed by surgery (T-S-Arm) and EGFR-TKI alone (T-Arm) were reviewed retrospectively in Shanghai Pulmonary Hospital (SPH). The chi-square test, Student’s t-test or Fisher’s exact test was performed for analysis of baseline characteristics. Progression-free survival (PFS) was estimated using the Kaplan-Meier analysis. Multivariate Cox regression analysis was used to identify independent predictors of progression. Results A total of 43 patients were divided into T-S-Arm (n = 21) and T-Arm (n = 22). Patients were well-balanced between the two arms. The majority of patients were female (n = 25, 58.1%), non-smokers (n = 35, 81.4%), first-generation of EGFR-TKI treatment (n = 39, 90.7%), and exon 19 deletions (19-DEL) (n = 26, 60.5%). The median diagnostic age was 63.0 years [interquartile range (IQR), 54.0-67.5 years). At the cut-off date with June 30th 2022, median follow-up time was 28 months (IQR, 20-39 months). Neoadjuvant EGFR-TKI treatment followed by radical surgery could significantly improve the median PFS compared with patients underwent EGFR-TKI alone (23.0 months vs 14.5 months, P = 0.002). Multivariate Cox regression analysis demonstrated that radical surgery (T-S-Arm vs. T-Arm, HR: 0.406; 95% CI: 0.207-0.793, P = 0.027) was the only independent predictor for disease progression. The stratified analysis demonstrated patients with N2 disease could benefit from radical surgery (HR, 0.258; 95% CI, 0.107-0.618), especially for patients harboring L858R mutation (HR, 0.188; 95% CI, 0.059-0.604). Conclusions For stage IIIB EGFRm NSCLC patients, the prognosis might be improved by neoadjuvant EGFR-TKI followed by radical surgery versus EGFR-TKI alone, especially for those with N2 disease and harboring L858R mutation.